UJI COBA PERANGKAP UDANG DENGAN BENTUK YANG BERBEDA (EXPERIMENTAL FISHING WITH TRAP PRAWN DIFFERENT FORM) - Irhamsyah Irhamsyah (Fish Scientiae, 2019)
This study aims to (1) know the difference between the catch of prawns from tamba and ayunan, and (2) to determine the catch other than prawn.The results, treatment A (tamba) gained as much as 52 prawns, with a total weight of 2,210 grams. Treatment B (ayunan modifications bamboo flooring), gained as much as 29 prawns, with a total weight of 180 grams. Total catch of prawns using swing modifications and add bamboo flooring for 16 days of observation was 81prawns with a total weight of 2,390 grams. Main types of catches fresh water prawn (Macrobrachium rosenbergii de Man) with a side of the catch is Lundu (Mystus Gulio) and Sapu-sapu (Hypostomusplecostomus).